Dr. Ernesto Galarza Scholarship Symposium Program 1995 - Chicano/Latino Faculty and Staff Association::::::::::::::: (2024)
Program for the 11th Annual Dr. Ernesto Galarza Symposium and Scholarship Ceremony, held at San Jose State University on Thursday, April 20, 1995 at 5:30 PM – 7:30 PM. The Master of Ceremonies was Damien Trijillo (KSTS Television, Channel 48 News). This event included a Social Hour, Opening Remarks by Ric Abeyta (Director of the Department of Public Safety, SJSU), Welcome by Dr. Robert L. Caret (President, SJSU), Keynote by Ms. Rose Guilbault (Public Affairs and Editorial Director, KGO Television, Channel 7), Presentation of Scholarships by Ms. Deanna Gonzales, and Closing Comments. Fourteen awards were presented: Pueblo de San José Kiwanis Club Scholarship (3 awards), Chicano/Latino Faculty and Staff Association Scholarship, Dr. Ernesto Galarza Endowment Scholarship, Cesar Chavez Memorial Scholarship, Latino Pride Scholarship – AT&T, Applied Materials, Inc., Nordstrom (4 awards), Dr. George Castro (College of Science SJSU)/IBM Scholarship (2 awards), Nu Alpha Kappa Fraternity Scholarship, and Calmeca Project Scholarship.